Comparative Quantification of Urban Physical Expansion’s Contribution to Green Spaces Change in Kisumu and Eldoret Towns of Kenya - Lagat, M.; Kiplagat , A.; Ng’etich, J. (Africa Environmental Review Journal, 2022)
Despite their importance, urban green spaces are under severe threat and urbanization has been shown to be the main driver. Unfortunately, not much is known about how urbanization has played a role in the decline and more so in the cities of Sub-Sahara Africa (SSA). This study therefore sought to fill this gap by studying Kisumu and Eldoret towns of Kenya as cases with the objective of quantifying the impact urbanization on green spaces availability. Using supervised classification technique, multi-temporal data dated 1989-2019 was extracted from selected Landsat images and error matrix used to check on the validity of data. Results showed that while Kisumu and Eldoret towns experienced tremendous physical growth, green spaces shrunk rapidly. Built-up areas were found to have expanded by 742.30% and 2199.06% in Kisumu and Eldoret respectively from 1989 to 2019 with green spaces shrinking by 50.92% in Kisumu. However, there was a slight increase of 32.11% in Eldoret in the period 1989 to 2019. Findings further showed urban physical growth going beyond the towns’ planned boundaries. This study therefore demonstrates that urbanization is a threat to urban green spaces and deliberate spatial planning interventions are needed urgently so that green spaces and associated benefits are protected to promote sustainability of urban areas.